2018
DOI: 10.1111/1460-6984.12416
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for children with phonological impairment: Knowledge, practices and intervention intensity in the UK

Abstract: The most commonly used intervention approaches identified in the current survey (i.e., speech discrimination, conventional minimal pairs and phonological awareness therapy) may be used eclectically by SLTs, which could impact upon the effectiveness and efficiency of treatment for phonological impairment. The current study also highlighted that almost half the participants always/often used traditional articulation therapy to remediate phonological impairment, even though this approach has been found to be less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 35 publications
3
39
1
1
Order By: Relevance
“…They concluded that detailed reporting of intervention intensity is required in future research to determine the optimal levels for effective treatment. Factors such as the frequency, dosage, location, duration and person delivering the intervention are all recognized to be crucial when investigating how intervention is delivered (Sugden et al, 2018;Hegarty et al, 2018;Roulstone et al, 2012;2015).…”
Section: Delivery Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that detailed reporting of intervention intensity is required in future research to determine the optimal levels for effective treatment. Factors such as the frequency, dosage, location, duration and person delivering the intervention are all recognized to be crucial when investigating how intervention is delivered (Sugden et al, 2018;Hegarty et al, 2018;Roulstone et al, 2012;2015).…”
Section: Delivery Of Interventionsmentioning
confidence: 99%
“…Meinusch & Romonath's (2011) systematic review of early language interventions for children with CP±L concluded that the involvement of caregivers in the therapeutic setting enhanced the child's language abilities. Other studies (Ha, 2015;Dobbelsteyn et al, 2014) Previous research has investigated intervention factors such as the frequency, dosage, location, duration and the person to deliver intervention, which are recognized to be important when studying how intervention is delivered (Hegarty et al, 2018;Roulstone et al, 2015;Roulstone et al, 2012). Participants described a multitude of intervention factors, which reflect resource availability and consideration of the individual needs of the child and their family.…”
Section: Intervention Approaches and Service Delivery Modelsmentioning
confidence: 99%
“…Given the high prevalence of the disorder, it is unsurprising that children with SSD comprise a large proportion of speech and language therapy caseloads worldwide (Hegarty et al . , McLeod and Baker ). Although there is no universally agreed upon system for classifying the different presentations of SSD, it is largely established that children with the disorder form a heterogeneous group (Waring and Knight ).…”
Section: Introductionmentioning
confidence: 96%
“…, Hegarty et al . , Sugden et al . , Brumbaugh and Smit ), with the child being provided with auditory information regarding the target sounds and their own productions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation